Evidence for the use of PRP in chronic midsubstance Achilles tendinopathy: A systematic review with meta-analysis. Issue 5 (July 2021) - Nauwelaers, An-Katrien; Van Oost, Loïc; Peers, Koen
Highlights: The use of PRP injections in the management of chronic midsubstance Achilles tendinopathy is increasing, but the efficacy is highly debated. Randomized controlled trials with a high level of methodological quality show no clear additional value of PRP. Whereas studies favoring PRP seem to have a higher risk of bias profile. PRP injections show no clear additional value in the management of chronic midsubstance AT, therefore the widespread use of PRP is questionable. Abstract: Background: Platelet-rich plasma (PRP) injections have been proposed as an additional therapy in the treatment of chronic midsubstance Achilles tendinopathy (AT). The use of PRP injections as pharmacological treatment added to a conservative approach has gained growing interest, but the efficacy remains highly debated. The varying methodological quality of the available studies may contribute to these contradictory results. The aim of this systematic review with meta-analysis was to establish the existing evidence of PRP injections for chronic midsubstance AT on the functional outcome, with a risk of bias assessment of each included study. Methods: According to the PRISMA guidelines systematic searches were performed in Embase, the Cochrane library and Pubmed on June 12, 2020 for relevant literature. Only clinical trials comparing PRP injections with placebo, additional to an eccentric training program, in midsubstance AT were included. The primary outcome was Victorian Institute of Sport Assessment - Achilles (VISA-A) score at 3, 6 and 12 months post-injection. Risk of bias was assessed using the Cochrane risk-of-bias tool for randomized trials (Rob 2). As secondary outcome we assessed reported changes in tendon structure after PRP injections. Results: A total of 367 studies were identified with the initial database search. Finally, four randomized controlled trials (RCTs) met inclusion criteria for systematic review and meta-analysis with data of 170 patients available for pooling. Results showed no difference in clinical outcome between the PRP and placebo group at different points in time using the VISA-A score as outcome parameter (3 months 0.23 (CI -0.45, 0.91); 6 months 0.83 (CI -0.26, 1.92); 12 months 0.83 (CI -0.77, 2.44)). The bias analysis showed a low or intermediate risk of bias profile for all studies which supports the good methodological quality of each included article. Finally, it is unclear whether PRP injections cause an improvement in tendon structure. However, no direct relationship between tendon structure and clinical presentation of AT could be found. Conclusion: PRP has no clear additional value in management of chronic midsubstance Achilles tendinopathy and therefore should not be used as a first-line treatment option.